Analysis Of The Influence Of Ethical Leadership And Employee Ethical Behavior On Innovative Work Behavior Mediated By Psychosocial Well-Being - Pramana Gunarso; Kusuma Chandra Kirana; Syamsul Hadi (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2025)
This research explores how ethical leadership and employee ethics influence innovative workplace behavior among office personnel, with psychological counseling serving as a mediating factor. Using a quantitative approach, the technique of saturated sampling is used to include all 192 employees in the study. SmartPLS is used for data analysis. The results indicate that there is no significant impact in relation to innovative work practices, either in terms of ethical leadership or ethical employees. However, Ethical Leadership and Ethical Behavior of Employees significantly and favorably impact psychological well-being. Not only that, but it also has a significant positive impact on innovative work practices and, on the other hand, strengthens the bonds between innovative work practices, ethical leadership, and ethical employees. This highlights the importance of a worker's psychological well-being in fostering innovation and emphasizes the need to strengthen psychological factors to increase employees' ability to innovate in an ethical work environment.